2022
DOI: 10.3389/fimmu.2022.847601
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization Combined With Immune Checkpoint Inhibitors and Tyrosine Kinase Inhibitors for Unresectable Hepatocellular Carcinoma: Efficacy and Systemic Immune Response

Abstract: BackgroundLocoregional therapy combined with systemic therapy can further improve the prognoses for HCC. However, the efficacy of TACE combined with ICIs and TKIs for HCC and whether this triple therapy can activate systemic immune response are still unknown.PurposeTo identify the efficacy of TACE+ICIs+TKIs for unresectable hepatocellular carcinoma (uHCC) and its effect on systemic immunity.Materials and MethodsThis single-center retrospective study was approved by the Institutional Review Board. From August 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 39 publications
(45 reference statements)
0
32
0
Order By: Relevance
“…On the other hand, systemic therapy is the key to improve the long-term prognosis, but unsatisfactory LC will impair the long-term survival advantage. Preclinical studies have identified the synergistic effect of TACE/HAIC and systemic therapy ( 20 , 21 ), which was also confirmed in practice of the combination of TACE and sorafenib ( 22 ), TACE and lenvatinib ( 23 ), HAIC and sorafenib ( 24 ), and HAIC plus lenvatinib and toripalimab ( 25 ), but it is not the end.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…On the other hand, systemic therapy is the key to improve the long-term prognosis, but unsatisfactory LC will impair the long-term survival advantage. Preclinical studies have identified the synergistic effect of TACE/HAIC and systemic therapy ( 20 , 21 ), which was also confirmed in practice of the combination of TACE and sorafenib ( 22 ), TACE and lenvatinib ( 23 ), HAIC and sorafenib ( 24 ), and HAIC plus lenvatinib and toripalimab ( 25 ), but it is not the end.…”
Section: Introductionmentioning
confidence: 80%
“…Yang et al. ( 20 ) firstly identified that the triple therapy could not only activate cell immunity but also stimulate humoral immunity, and circulating Ig G, Ig λ, and Ig κ could serve as potential biomarkers of triple therapy. In the future, more attention should be paid on the triple combination modality for uHCC, especially for those with a strong willingness to receive radical resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunotarget therapy with a median PFS of 4.6-6.8 months and ORR of 20-30% still failed to meet clinical needs 17 . In recent years, encouraging results have been made regarding the e cacy of the triple combination, and the ORR and DCR were approximately 50%-70% and 80%-100%, respectively 18,19 . Unfortunately, these results were from studies on small sample populations with fewer than 50 participants.…”
Section: Discussionmentioning
confidence: 99%